Family practitioners' top medical priorities when managing patients with multimorbidity: a cross-sectional study. Issue 1 (2019) - Herzig, Lilli; Mueller, Yolanda; Haller, Dagmar M; Zeller, Andreas; Neuner-Jehle, Stefan; Deruaz-Luyet, Anouk; Cohidon, Christine; Burnand, Bernard; Zuchuat, Jean-Christophe
No abstract available